Exposure to maltreatment and urban violence in children working on the streets in São Paulo, Brazil: Factors associated with street work - Mello, Andrea F.; Maciel, Mariana R.; Fossaluza, Victor [UNESP]; de Paula, Cristiane S.; Grassi-Oliveira, Rodrigo; Cavalcante-Nóbrega, Luciana P.; Cividanes, Giuliana C.; Soussumi, Yusaku; Soussumi, Sonia P.; Perissinotti, Dirce N. M.; Bordin, Isabel A.; Mello, Marcelo F.; et al. (EDITORA SCIENTIFIC, 2014)
Objective: To quantitatively study the exposure to childhood maltreatment and urban violence in children from families with at least one child working on the streets and to investigate the relationship between these factors and street work. Methods: Families who participated in a nongovernmental organization (NGO) program to eliminate child labor were included. Data concerning sociodemographic characteristics, punishment methods used in the family environment against the children, five types of abuse and neglect perpetrated by the caregivers, urban violence exposure and family functioning were collected. Results: The sample included 126 children who were working on the streets and 65 siblings who were not working on the streets. Caregivers reported high levels of severe physical punishment. The children reported high levels of abuse and neglect, and high levels of urban violence exposure. The families showed a predominance of dysfunctional and unsatisfactory relationships. A multiple logistic regression model showed that age older than 12 years and severe physical punishment at home were associated with street work. Conclusion: Interventions to decrease the risk of child street work should be family-focused and should aim to reduce violence in the family environment. © 2014 Associação Brasileira de Psiquiatria.
Keywords: Child abuse; Child maltreatment; Family functioning; Street children; Urban violence